Business Integration Analysis of Aquaponic Technology on Catfish (Clarias sp.) Cultivation in The Strengthening of The Business MSME Scale in Pandemic Covid-19 - Muhiddin Sirat; Darma Yuliana; Deny Sapto Chondro Utomo; Muhammad Mirandy Pratama Sirat; Ratna Ermawati (Jurnal Ekonomi Pembangunan, 2022)
The aim of this study was analyzed the effort to implement the integration of aquaponic technology in conventional fish cultivation. The study was conducted for 6 months (May - October 2021) in the Mandiri Sentosa fish farming unit in Marga Agung Village, Jati Agung District, South Lampung Regency. Experimental research with quantitative methods with descriptive analysis of two treatments is the analysis of the feasibility of catfish cultivation business that has not been integrated with Aquaponik technology (P0) and which has been integrated with Aquaponic technology (P1). Each treatment pool with a 2,000 catfish density with 5-7 cm/fish marked size was maintained for 3 months for harvest. The integration of aquaponic technology in the treatment pool (P1) with the number of vegetable seeds of lettuce was 100 seeds per treatment pool. Quantitative method was doing by business analysis to determine the activities of catfish cultivation business (Clarias sp.) Has benefits and deserves to be developed from the parameters of business cost analysis, depreciation, acceptance analysis, net cash flow (net cash flow), R/C ratio, B/C ratio, Break-Even Point (BEP), Payback Period. The conclusion of this research was the farming business based on aquaponic technology in Catfish (Clarias sp.) cultivation was profitable business or very suitable to be developed.